2022
DOI: 10.3389/fvets.2022.913841
|View full text |Cite
|
Sign up to set email alerts
|

The miR-216/miR-217 Cluster Regulates Lipid Metabolism in Laying Hens With Fatty Liver Syndrome via PPAR/SREBP Signaling Pathway

Abstract: Fatty liver syndrome (FLS), a common metabolic disease in laying hens, caused by excessive hepatic fat deposition is a bottleneck in the poultry industry. However, no specific therapeutic methods have been developed. Evidence suggests that microRNAs (miRNAs) are essential for liver lipid metabolism and homeostasis, providing strong evidence for targeting miRNAs as a potential treatment option for liver diseases. However, the roles of miRNAs in the pathogenesis of FLS remain unclear. In present study, RNA-seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In avian, the yolk precursor formation and lipid metabolism depends on the regulation of E 2 and its downstream signal pathways ( Cui et al, 2020 ). Previous studies indicated that transcription levels of vitellogenins Ⅱ ( VTGⅡ ), apolipoprotein B ( ApoB ), apolipoprotein VLDL Ⅱ ( ApoVLDL Ⅱ ), sterol regulatory element binding transcription factor 1 ( SREBF1 ), diacylglycerol acyltransferase 2 ( DGAT2 ), fatty acid synthase ( FASN ), microsomal triglyceride transfer protein ( MTTP ), and peroxisome proliferator activated receptor alpha ( PPARα ) in liver tissues are positively correlated with lipid metabolism and egg yolk formation in hens ( Liu et al, 2016 ; Wang et al, 2016 ; Nii et al, 2020 ; Tolba et al, 2020 ; Zhu et al, 2022 ). Down-regulation of lipoprotein lipase ( LPL ) expression alleviates excessive lipid accumulation in liver tissues ( Beckford et al, 2017 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In avian, the yolk precursor formation and lipid metabolism depends on the regulation of E 2 and its downstream signal pathways ( Cui et al, 2020 ). Previous studies indicated that transcription levels of vitellogenins Ⅱ ( VTGⅡ ), apolipoprotein B ( ApoB ), apolipoprotein VLDL Ⅱ ( ApoVLDL Ⅱ ), sterol regulatory element binding transcription factor 1 ( SREBF1 ), diacylglycerol acyltransferase 2 ( DGAT2 ), fatty acid synthase ( FASN ), microsomal triglyceride transfer protein ( MTTP ), and peroxisome proliferator activated receptor alpha ( PPARα ) in liver tissues are positively correlated with lipid metabolism and egg yolk formation in hens ( Liu et al, 2016 ; Wang et al, 2016 ; Nii et al, 2020 ; Tolba et al, 2020 ; Zhu et al, 2022 ). Down-regulation of lipoprotein lipase ( LPL ) expression alleviates excessive lipid accumulation in liver tissues ( Beckford et al, 2017 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver samples were embedded in Tissue-Tek OCT embedding compound, frozen on dry ice, cut into 8-μm-thick frozen sections, and stained with an Oil Red Staining kit (Solarbio, Beijing, China). LMH cells were cultured with 1 mM free FAs (FFAs), as we described previously [ 21 ], and a 10-fold dilution of L. salivarius SNK-6 medium supernatant was added and incubated for 24 h. Cells were collected and fixed in 4% paraformaldehyde, stained by Oil Red O Staining kit (Solarbio), and observed under an electron microscope (Nikon). Data were analyzed by Image-Pro Plus 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…SREBP is a major transcription factor transactivating lipogenesis-related genes (e.g., FASN, ACACA) [118], and its regulation by microRNAs has been extensively documented in the context of NAFLD [119,120]. As described above, the downregulation of miR-203 expression in the liver of mice fed an alcoholic diet [37], is directly responsible for the upregulation of Lipin-1 [37], which can promote β-oxidation and inhibit SREBP-1 signaling.…”
Section: Srebp Signalingmentioning
confidence: 99%